Analisis Yuridis Penggunaan Cryptocurrency sebagai Sarana Pendanaan Aksi Terorisme di Indonesia Beserta Tantangan dalam Penegakan Hukum (Pusat Riset dan Inovasi Nasional, 2026)
The development of financial technology has led to the emergence of cryptocurrency as a decentralized digital instrument that enables fast and cross-border financial transactions. While this technology offers efficiency and flexibility in digital financial activities, it also creates opportunities for misuse in various forms of crime, including terrorist financing. This study aims to analyze the use of cryptocurrency as a means of financing terrorist activities in Indonesia, examine the existing legal framework governing terrorist financing, and identify the challenges faced in law enforcement. This research employs a normative legal method using statutory, conceptual, and case study approaches. The findings indicate that the use of cryptocurrency as a medium for terrorist financing still fulfills the elements of a criminal offense as regulated under Law Number 9 of 2013 concerning the Prevention and Eradication of Terrorism Financing. However, the characteristics of cryptocurrency, such as anonymity, decentralization, and cross-border transactions, create significant challenges in the processes of evidence gathering, transaction tracing, and identification of perpetrators. In addition, there is a regulatory gap between the recognition of crypto assets as economic commodities and the supervision of their potential misuse for terrorist financing. Therefore, stronger regulations are needed to explicitly integrate crypto assets into the terrorist financing prevention regime, along with improving the capacity of law enforcement agencies in blockchain transaction analysis and strengthening international cooperation to enhance the effectiveness of law enforcement in the digital economy era.